2005
DOI: 10.1088/0953-4075/38/8/015
|View full text |Cite
|
Sign up to set email alerts
|

On the behaviour of the (e, 3e) total cross section for helium at high and intermediate energies

Abstract: Applying the animated beam method the total cross sections (TCS) for double ionization (DI) of helium by electrons are measured in the collision energy region from threshold to 3 keV. The TCS for the same process are calculated at intermediate and high incident energies in the first Born approximation (FBA). The radial and angular correlations between the bound electrons and repulsion between the ejected electrons are accounted. In order to go beyond the FBA the scattered electron is considered as a particle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In addition, the scattered electron being, by definition, the most energetic electron in the final state, we have followed the recommendations of Defrance et al [54] and Bahati et al [55] and defined the upper limits of the integration E 1 max and E 2 max as…”
Section: -4mentioning
confidence: 99%
“…In addition, the scattered electron being, by definition, the most energetic electron in the final state, we have followed the recommendations of Defrance et al [54] and Bahati et al [55] and defined the upper limits of the integration E 1 max and E 2 max as…”
Section: -4mentioning
confidence: 99%
“…Perhaps, it should be also emphasized that the compact trial functions are not only valuable in order to gain understanding of quantum mechanics of compact few-body systems-bound state-but they are also of interest to the collision community [12]. It turns out that simple but accurate wave functions are very useful as a starting point in the calculation of double ionization cross section by electron or radiation impact as was indicated as early as by Chandrasekhar at 1944 [13], as for recent references see, for example, [14,15] and references therein. Highly sophisticated wavefunctions with large numbers of terms and parameters are frequently non-practical since they require time-demanding computer codes to evaluate cross sections.…”
mentioning
confidence: 99%
“…Under these conditions, the initial state of the system is characterized by the product of an incident plane wave with a molecular target wave function while the final state is described by the product of a scattered plane wave with two independent Coulomb wave functions as well as an approximate expression of the Gamov factor for modeling the electron-electron repulsion [24,25]. Finally, in order to go beyond the domain of validity of the first Born approximation and then to extend the current water molecule double ionization modeling down to the intermediate energy regime, we followed the recommendations of Behati et al who suggested to use an approximate Coulomb wave function of effective charge Z* to represent the scattered electron in the field created by the water nucleus together with the two ejected electrons [26][27][28]. In their approach, the authors simply replaced the scattered electron Coulomb wave function by the first term of the whole hypergeometric series that may then be seen as a multiplicative factor, which characterizes the influence of the effective Coulomb field on the scattered electron being not far from the target nucleus.…”
mentioning
confidence: 99%
“…Then, benefiting from the selectivity rules of the complex harmonics used in the description of the molecular wave function, we easily access to triply differential cross sections, which are then numerically integrated over the solid angle Qs as well as the ejected energies £j and E2 to provide orientation-dependent total cross sections defined as [26] In Eq. (3), let us note that the upper limits of the integration £ j max and E2mm are defined by E]mm = (£; -/ 2+) and £ 2max = £l max ~ £l with £/ = / 2+ + Es + £ , + £ 2 [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation